PENGARUH NILAI BELANJA HEDONIS, SUASANA TOKO, DAN PROMOSI PENJUALAN TERHADAP PEMBELIAN IMPULSIF - Listyowati, Dwi; Fitri, Indah Sagita; Dewi, Sita; Dewi, Diana Setiyo; Wibowo, Kuncoro (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The retail industry in Indonesia is growing rapidly. Retail stores offer convenience, comfort and good service to consumers. Consumers themselves in shopping are not only based on logic but also emotions. On the basis of emotions, consumers can suddenly want to buy products without planning, this is known as impulse buying. The emotional impulse that makes consumers want to buy products abruptly can be based on pleasure, enjoyment when shopping. Hedonic shopping values indicate that there is pleasure, enjoyment, fantasy in shopping. Consumers can also make impulse purchases because they are carried away by the atmosphere of the store atmosphere. A comfortable store atmosphere can encourage consumers to buy products without planning. It cannot be denied that consumers will buy products because of product promotions or promotions from the store. Sales promotions in the form of discounts, cashback, sweepstakes or prizes can encourage consumers to buy the products offered without thinking again, or impulse purchases are made because of sales promotions. This study aims to determine the effect of hedonic shopping value, store atmosphere, sales promotion on impulse purchases, both partially and simultaneously. The population of this study were Miniso Mall Kota Kasablanka customers. The sample was 86 respondents. The data used is primary data. Data analysis using multiple linear regression and correlation analysis. The results showed that hedonic shopping value and sales promotion partially had a positive and significant effect on impulse purchases at Miniso Mall Kota Kasablanka customers. While the store atmosphere has no effect. Simultaneously hedonic shopping value, store atmosphere, sales promotion have a significant effect on impulse purchases at Miniso Mall Kota Kasablanka customers. The contribution of hedonic shopping value, store atmosphere, sales promotion in influencing impulse purchases of Miniso Mall Kota Kasablanka customers is 65.1%.